Is Religion Compatible with Modernity? An Overview on Modernity’s Measurements And its Relation to Religion - Sukron Kamil (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2018)
This paper aims to elaborate the measurements of modernity and its relation to religion. In the Third World, modernity is often measured by unclear measurements, and in some cases, some of the attitudes of certain circles in the West now also appear to be at odds with modernity. Based on a literature survey, this paper finds that modernity is a condition, not as a specific marker of a certain period and region. Modernity points not only to the West, but also to non-West, because modernity can be measured by: capitalism as an economic rationality; mass production-based industries and the existance of industry mentality; urban population pressure and its medical control; secular and humanist nation state; democratic country; rational bureaucracy, the state's rule of law, military-based technology; and empirical science and rationalism. Even so, for a secular state, it does not require the latest modernity that should alienate religion absolutely in a public sphere. Religion is possible to be in the public sphere, if it could be debated rationally and does not discriminate minorities as certainly religion is now more rational. Religion is also possible to contest with other issues in a public sphere in the free market in a democratic political system and can be a civil society force; in addition, some religions do not mind with secularization in the sense of sociological rationalization.DOI: 10.15408/insaniyat.v2i2.7260